2008
DOI: 10.1074/jbc.m803348200
|View full text |Cite
|
Sign up to set email alerts
|

Re-evaluating the Roles of Proposed Modulators of Mammalian Target of Rapamycin Complex 1 (mTORC1) Signaling

Abstract: Signaling through mammalian target of rapamycin complex 1 (mTORC1) is stimulated by amino acids and insulin. Insulin inactivates TSC1/2, the GTPase-activator complex for Rheb, and Rheb⅐GTP activates mTORC1. It is not clear how amino acids regulate mTORC1. FKBP38 (immunophilin FK506-binding protein, 38 kDa), was recently reported to exert a negative effect on mTORC1 function that is relieved by its binding to Rheb⅐GTP. We confirm that Rheb binds wild type FKBP38, but inactive Rheb mutants showed contrasting abi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
99
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(108 citation statements)
references
References 56 publications
6
99
3
Order By: Relevance
“…5). These observations are supported by a recent report (44), which argued that FKBP38 did not inhibit mTORC1 signaling. Taking these results together, we conclude that RalA participates in mTORC1 regulation independently to FKBP38 (Fig.…”
Section: Resultssupporting
confidence: 80%
“…5). These observations are supported by a recent report (44), which argued that FKBP38 did not inhibit mTORC1 signaling. Taking these results together, we conclude that RalA participates in mTORC1 regulation independently to FKBP38 (Fig.…”
Section: Resultssupporting
confidence: 80%
“…The first description of a NMR structure of TCTP had revealed a similarity of TCTP to the MSS4/DSS4 proteins, which bind to the Rab family of small GTPases (Thaw et al 2001). Thus, the idea that TCTP acts as a GEF for Rheb appeared attractive, but it remains controversial, since later studies failed to support the results described for Drosophila: We found that reducing TCTP levels did not reproducibly affect mTORC1 signalling in human cells, and we were unable to detect a stable interaction between TCTP and Rheb (Wang et al 2008). Similarly, Rehmann and colleagues did not detect GEF activity of TCTP for Rheb or any interaction between TCTP and Rheb (Rehmann et al 2008).…”
Section: Tctp and Cell Growth Regulationmentioning
confidence: 58%
“…Also, Hsu et al described TCTP in Drosophila as an activator of the small GTPase Rheb, an upstream activator of the mTORC1 pathway, and based on this, implicated TCTP in growth regulation (Hsu et al 2007). However, other follow-up studies could not confirm some of the findings in mammalian cells (Wang et al 2008;Rehmann et al 2008). Thus, while some studies indicate that TCTP could act as a growth-regulatory protein, these ideas and the mechanisms involved need further consolidation.…”
Section: Mechanistic Involvement In Cancer Progressionmentioning
confidence: 89%
“…This observation is consistent with the demonstration that TCTP overexpression in mice results in systemic hypertension (Kim et al, 2008b); (2) TCTP interacts with protein synthesis elongation factor eEF1A and negatively regulates the guanosine-nucleotide-exchange reaction on eEF1A (Cans et al, 2003); (3) a study using gene knockdown in Drosophila reported the activity of TCTP as a guanine-nucleotide-exchange factor for the small GTPase, Rheb, and indicated involvement of TCTP in the target of rapamycin (TOR) signalling pathway (Hsu et al, 2007); however, recent results from our own (Wang et al, 2008) and two other laboratories (Chen et al, 2007;Rehmann et al, 2008) are not compatible with this conclusion.…”
Section: Introductionmentioning
confidence: 98%